Find ∫(x^3+x^2+6)dx.

∫(x3+x2+6)dx= ∫x3dx +∫x2dx+∫6dx =x4/4 +x3/3 +6x+C.

Answered by Georgiana I. Maths tutor

5638 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has equation y = x^3 - 3x^2 -24x + 5, find the x co-ordinates of the two stationary points of the curve and hence determine whether they are maximum or minimum points.


How do I prove (x-2) is a factor of the function f(x) = x^2-4x+4?


Find the gradient of the curve y=sin(x^2) + e^(x) at the point x= sqrt(pi)


Express 4x/(x^2-9)-2/(x+3) as a single fraction in its simplest form


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences